Ambiverts Potentially Have Better Orienting Response than Extraverts in Visual Oddball Paradigm of Event Related Potential - Yusoff, Nasir; Shan Tai, Yan; Napisah Muhammad, Saidah; Reza, Faruque (International Journal of Engineering and Technology, 2018)
Background: Differences in personality may indicate dissimilarity in the process of cognition.  Objectives: To investigate and compare the neural substrate of P300 component evoked between ambiverts and extraverts in visual oddball paradigm of Event Related Potential study.  Methods: Forty undergraduate medical students from Universiti Sains Malaysia (USM) were recruited and screened for personality by using USM Personality Inventory (USMaP-i).  In the Event Related Potential (ERP) session, participants (N=19 ambiverts and 20 extraverts) completed a visual oddball paradigm in counterbalanced order.  Results: Mann Whitney Test showed that, compared to ambiverts, the extraverts showed diminished P300 amplitude at the Fz electrode, but not at other electrodes. Conclusion: Ambiverts might have better orienting response than extraverts.